2005
DOI: 10.1016/j.snb.2004.05.066
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy k-NN applied to moulds detection

Abstract: The possibility to detect Aspergillus versicolor growing on different building materials by a metal oxide sensor array is studied. Results show that an accurate classification rate of 89 ± 3% can be obtained combining an extended linear discriminant analysis plus a fuzzy k-NN classifier. The classification ability of the classifier is assessed within the dataset by cross validation and also in a second dataset collected 5 months later. There is a slight decrease in the classification performance for all the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…For this purpose a Mahalanobis classifier was applied on the raw data. The obtained results are on the same order than the ones seen in the previous paper [19]. Although the same classifiers as in [19] were considered; namely k-NN, fuzzy-kNN with different initial membership functions on dimensional reduced space and on raw data (a review of Fuzzy k-NN can be found in our previous paper [19]) we found that the application of complex classifiers on our small database did not provide any advantage; the obtained classification rates were not in general better than the ones obtained using the Mahalanobis classifier.…”
Section: Signal and Data Processingsupporting
confidence: 85%
See 1 more Smart Citation
“…For this purpose a Mahalanobis classifier was applied on the raw data. The obtained results are on the same order than the ones seen in the previous paper [19]. Although the same classifiers as in [19] were considered; namely k-NN, fuzzy-kNN with different initial membership functions on dimensional reduced space and on raw data (a review of Fuzzy k-NN can be found in our previous paper [19]) we found that the application of complex classifiers on our small database did not provide any advantage; the obtained classification rates were not in general better than the ones obtained using the Mahalanobis classifier.…”
Section: Signal and Data Processingsupporting
confidence: 85%
“…The authors have already addressed the detection of a single mould species, namely Aspergillus versicolor, in a previous paper [19]. In that paper a table with a detailed list of VOCs produced by moulds can be found.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, clear symptoms of infestation significantly exceeding the standard values can already be observed. Two solutions can be employed in order to improve LOD of devices: preconcentration on solid sorbents [140] as well as decreasing the sample to air volume ratio by tightly sealing it in a small vessel. The techniques of trap and desorption for LOD enhancement were adopted from gas chromatography.…”
Section: Gas Sensor Arraymentioning
confidence: 99%
“…New techniques appear but they still require laboratory analyses, are time consuming and expensive. At the end of the 1990s and in the early 2000's, an approach based on analysis of MVOCs (Microbial Volatiles Organics Compounds) have been studied [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%